Exploring Technological Gaps in the Implementation of Auto-Electricity/Electronics: Aligning Motor Vehicle Mechanic Programs in Nigeria with Modern Automobile Industry Needs - Muoghalu, Nzube; Ahmad, Adnan (Journal of Technical Education and Training, 2025)
This study explores the technological gaps in the implementation of the Motor Vehicle Mechanic (MVM) program, with a particular focus on auto-electricity and electronics in Nigerian technical colleges. Using a qualitative research design, data was collected through semi-structured interviews with 20 stakeholders, including MVM administrators, teachers across nine technical colleges in Delta State and master craftsmen, and managers from the automotive industries in Nigeria. Reflexive thematic analysis, supported by NVivo 14 software was utilized to identified key themes that illustrate critical gaps impeding the program’s ability to meet industry standards. Findings revealed gaps in curriculum alignment with evolving industry practices, outdated teaching and learning resources, insufficient cutting-edge equipment and tools, and the limited technological expertise of teachers. Furthermore, the study highlighted a lack of industrial partnerships necessary for experiential learning and exposure to modern automotive technologies, such as electric and hybrid vehicles. These deficiencies hinder the development of practical skills required for maintaining contemporary vehicles. The study emphasizes the urgent need for curriculum reform, enhanced teacher training, and strengthened collaboration with industry stakeholders to bridge these gaps. Addressing these challenges is essential for equipping MVM graduates with relevant competencies, ultimately aligning technical training programs with the demands of the modern automotive sector and improving graduates’ employability in Nigeria’s evolving labour market.